A novel chevron notched short rod bend method for measuring the mode I fracture toughness of rocks. (1st March 2018) - Wei, Ming-Dong; Dai, Feng; Xu, Nu-Wen; Liu, Yi; Zhao, Tao
Highlights: A novel CNSRB method was proposed for measuring mode I fracture toughness. The CNSRB method has obvious advantages compared with the ISRM-suggested SR method. The CNSRB method was proved reliable both experimentally and theoretically. The CNSRB method contributes to investigating fracture toughness anisotropy from a single rock core. The CNSRB method can estimate the fracture toughness with zero T-stress. Abstract: A novel chevron notched short rod bend (CNSRB) method is developed for measuring the mode I fracture toughness ( K Ic ) of rocks. Similar to the conventional short rod (SR) method suggested by the International Society for Rock Mechanics (ISRM), the proposed CNSRB method can also measure the fracture toughness along axial directions of rock cores. Moreover, the CNSRB has obvious advantages compared with the SR method, such as simpler installing and testing procedure, lower requirement on testing machine, higher failure load and lower required amount of intact rock core. To assess the reliability of the CNSRB method, K Ic results of CNSRB specimens and ISRM-suggested chevron bend (CB) specimens are both experimentally and theoretically compared. Laboratory tests on two rock types indicate that the CNSRB method can produce K Ic values comparable to those measured using the CB method. Moreover, theoretical predictions based on an extended maximum tangential strain (EMTSN) criterion show that, K Ic of the CNSRB specimen is closer to that of the CB specimen than that of the SR specimen, which inherently yields higher fracture toughness results than other ISRM-suggested specimens. Therefore, the CNSRB method can be reliably used to measure the mode I fracture toughness of rocks. Most importantly, accompanied with other test methods (e.g., CB), the proposed CNSRB method contributes to forming a complete set of methods for investigating fracture toughness anisotropy from a single rock core.